Effect of pH on production of virulence factors by biofilm cells of Pseudomonas aeruginosa - Harjai, K; Khandwahaa, R K; Mittal, R; Yadav, V; Gupta, V; Sharma, S (Folia microbiologica, 2005)
Effect of pH on production of extracellular virulence factors of Pseudomonas aeruginosa grown on catheter in biofilm was determined. Alginate and proteinase production was higher at pH 8; in contrast, siderophores (pyochelin and pyoverdin) were synthesized more intensively at pH 5.
Keywords: siderofory; Pseudomonas Infections; algináty; Virulence Factors; Hydrogen-Ion Concentration; kultivační média speciální; kyselina glukuronová; kyseliny hexuronové; Hexuronic Acids; bakteriální proteiny; Bacterial Proteins; lidé; Culture Media, Conditioned; proteasy; Peptide Hydrolases; pseudomonádové infekce; Alginates; Pseudomonas aeruginosa; moč; Siderophores; Glucuronic Acid; biofilmy; koncentrace vodíkových iontů; Biofilms; Urine; faktory virulence; Humans